2006
DOI: 10.1111/j.1439-0434.2006.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monoterpenes on Lipid Composition and Sclerotial Development of Sclerotium cepivorum Berk.

Abstract: Monoterpenes have antifungal activity on pathogenic fungi. The purpose of this study was to examine the effect of seven monoterpenes on phospholipid and sterol composition of Sclerotium cepivorum Berk as well as lipid peroxidation of mycelia and sclerotia development. Most of the monoterpenes increased the ergosterol content with a consequent diminution in the phospholipid/sterol ratio. This ratio was significantly decreased by the thymol treatment. When the fungus was grown in the presence of thymol or borneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 54 publications
(62 reference statements)
3
44
0
3
Order By: Relevance
“…Comprehensive studies focusing on the physiology and chemical composition of R. solani sclerotia would provide useful information that could be exploited in the implementation of effective disease control measures. Generally, studies on chemical composition of sclerotial fungi have shown that carbohydrates, proteins, lipids, fatty and amino acids, melanin-like pigments, and b-carotene are the main components (Chet and Henis 1975;Huang 1983;Abo Ellil 1999;Zervoudakis et al 2003;Lucini et al 2006). Despite these findings, there are no in-depth studies on the chemical composition of R. solani sclerotia considering that these bodies represent a key element in R. solani survival strategy.…”
Section: Introductionmentioning
confidence: 92%
“…Comprehensive studies focusing on the physiology and chemical composition of R. solani sclerotia would provide useful information that could be exploited in the implementation of effective disease control measures. Generally, studies on chemical composition of sclerotial fungi have shown that carbohydrates, proteins, lipids, fatty and amino acids, melanin-like pigments, and b-carotene are the main components (Chet and Henis 1975;Huang 1983;Abo Ellil 1999;Zervoudakis et al 2003;Lucini et al 2006). Despite these findings, there are no in-depth studies on the chemical composition of R. solani sclerotia considering that these bodies represent a key element in R. solani survival strategy.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, Lucini et al (2006) indicated mycelial growth inhibition is caused by the monoterpenes present in the EOs. These components could increase the concentration of lipidic peroxides such as hydroxyl, alkoxyl, and alkoperoxyl radicals, which leads to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…-ATPase pumping membrane, so producing a flux of protons toward the cell, exterior which induces changes in the cells and, ultimately, their death. Besides, several authors (Lucini et al 2006;Cristani et al 2007;Viuda-Martos et al 2008;Tatsadjieu et al 2009) reported that the antimicrobial activity is related to ability of terpenes to affect not only permeability but also other functions of cell membranes, these compounds might cross the cell membranes, thus penetrating into the interior of the cell and interacting with critical intracellular sites. In addition, Daferera et al (2000) reported that the fungitoxic activity of essential oils may have been due to formation of hydrogen bonds between the hydroxyl group of oil phenols and active sites of target enzymes.…”
Section: S Arvensismentioning
confidence: 98%